Communication strategies for earning trust in climate change debates. (11th November 2013) - Goodwin, Jean; Dahlstrom, Michael F.
Abstract : Climate scientists need the trust of lay audiences if they are to share their knowledge. But significant audience segments—those doubtful or dismissive of climate change—distrust climate scientists. In response, climate scientists can undertake one of two general communication strategies for enhancing trust, each appealing to one of two broad types of cognitive processing mechanisms. In the first, the communicator displays traits like humor, attractiveness, vigorous delivery, and likeability that audiences use as heuristics in determining whom to trust. But this strategy is unlikely to be successful with the very audiences who are its main targets, since those audiences will be primed to employ a more analytic and critical approach to assessing trustworthiness. In the second communicative strategy, the communicator earns trust by undertaking burdens and commitments and making herself vulnerable in ways her audience can enforce. This vulnerability signals her trustworthiness, since the audience can reason that she would not undertake such risks unless she was confident in what she was saying. Climate scientists have a variety of ways of making themselves vulnerable, including committing themselves to engaging with doubtful and dismissive audiences, undertaking burdens of proof to argue with them, empowering audiences to assess the science themselves, admitting error, and focusing on small issues. Overall, when adopting the second strategy, climate scientists must extend trust in order to earn trust, committing themselves to an on‐going relationship within which their true trustworthiness will become apparent. WIREs Clim Change 2014, 5:151–160. doi: 10.1002/wcc.262 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Communication Social Status of Climate Change Knowledge > Knowledge and Practice